ADVERSE CHILDHOOD EXPERIENCES: CONTRIBUTIONS OF PSYCHOPEDAGOGY TO THE RESIGNIFICATION OF TRAUMA - Barbosa de Morais, Weslley; Litwinczuk, Lilian; Paco Carvalho Pinto, Fernanda (Revista Gênero e Interdisciplinaridade, 2022)
In this article, we will dialogue from a central concern: The importance of access to Psychopedagogy to assist in the re-signification of childhood traumas. Adverse childhood experiences (ACEs) are traumatic situations that affect childhood and therefore human development. Psychopedagogy is a field of knowledge that is characterized as multidisciplinary, that is, that receives influence from several other areas of knowledge to build the theoretical and practical validity of its ideas. The purpose of this essay is to discuss, from the psychopedagogical perspective, possible elements that make it possible to overcome and redefine childhood traumas. The need for a multidisciplinary team for an effective treatment of these deep-seated traumas is founded, but above all, a team that has a professional who has psychopedagogical knowledge. It is understood that it is necessary to reflect and act on traumatic situations effectively, therefore, we will present fundamental themes for these debates in order to sustain the arguments in a valid manner. Through this text, it is intended to highlight the problem of adverse experiences in childhood and relate them to psychopedagogical science. We will use Neuroscience as a guiding field of knowledge, as well as Jorge Visca’s writings as a central theorist of Psychopedagogy.